Територіальні особливості розташування поселень за експозицією схилів на території Північної Бессарабії - Круль, Галина Ярославівна; Круль, Володимир Петрович; Григор'єва, Галина Володимирівна (Чернівецький національний університет імені Юрія Федьковича, 2018)
The article considers the location of settlements by the direction slopes of Northern Bessarabia within the Dniester and Prut river basins. An analysis was made for all 134 settlements in the region, and for 33 of them it was conducted according to their parts. Placement patterns for all settlements, for settlements with archaeological cultures and for "new" settlements (without traces of primitive life) were established. It was found that the northern slopes of the Dniester river basin and the south-eastern slopes of the Prut river basin are the territories of the greatest concentration of ancient settlements. For the "new" settlements on the Prut lands, the east-south direction prevailed, and in the Dniester territories, it shifted to the eastern slopes.
The territorial features of the location of settlements in the exposure of slopes in the territory of North Bessarabia
Keywords: напрям схилу; Північна Бессарабія; експозиція схилу; населений пункт; поселення